A simplified GMP-compliant cassette synthesis for ruthenium-mediated 18F-deoxyfluorination of [18F]FPATPP from a phenolic precursor - Rajala, Noora A.; Kerminen, Edla K.; Salo, Simo A.; Väkiparta, Melina J. J.; Kirjavainen, Anna K. (Elsevier, 2025)
Ruthenium-mediated 18F-deoxyfluorination of phenols is a fairly new, but highly underutilized, labeling method option of tracers for positron emission tomography (PET). Most of the published methods are directed toward peptide syntheses and include extensive preparation steps. This study aimed to simplify ruthenium-mediated 18Fdeoxyfluorination of [18F]FPATPP by using the TRASIS AllinOne synthesis platform. This protocol takes minimal preparation time (1 h) and applies a straightforward synthesis that can be used to produce tracers from their electron-rich phenolic precursors bearing protic functional groups such as alcohols and amines. The new simplified cassette method afforded a novel cannabinoid receptor 1 specific tracer [18F]FPATPP with a radiochemical yield of 34 ± 2 %, radiochemical purity of >= 97 %, and a molar activity of 620 ± 75 GBq/µmol. The total synthesis time was 55 min. In addition, we developed an attachable accessory compatible with TRASIS AllinOne to enable needle movement to enhance the synthesis yield. Our results broaden the possibilities of a cassette based synthesis development for 18F-labeled molecules and bridge the gap between research and GMP compatible synthesis methods.